Aberrant TNF secretion by whole blood in healthy subjects with a history of reactive arthritis: time course in adherent and non-adherent cultures. Issue 3 (17th August 2005) - Anttonen, K; Orpana, A; Leirisalo-Repo, M; Repo, H
Abstract : Background: The pathogenesis of reactive arthritis (ReA) apparently involves aberrations in innate immune functions such as monocyte tumour necrosis factor (TNF) generation. Objective: To investigate TNF production in healthy subjects with previous yersinia triggered reactive arthritis. Methods: The study comprised HLA-B27 positive subjects with previous reactive arthritis (B27+ReA+), and B27+ReA− and B27−ReA− subjects (n = 15 each). Whole blood TNF production was induced by lipopolysaccharide (LPS), which binds to CD14/TLR4 on the monocyte surface, or by a combination of phorbol 12-myristate 13-acetate (PMA) and Ca 2+ ionophore A23187, which activates monocytes independently of cell surface receptors. To further evaluate the possible role of adhesion mediated signalling on TNF production, blood samples were incubated in adherent or non-adherent conditions. TNF levels in culture supernatants were measured using an automated immunoassay analyser. The CD14 (−159)C/T genotype was determined by a cycle minisequencing method. Results: B27+ReA+ supernatants had higher TNF levels than B27+ReA− supernatants in PMA/A23187 wells in two hour (p = 0.004) and four hour cultures (p = 0.001). Rapid initial TNF release took place in adherent but not in non-adherent conditions. This adhesion associated difference was greater in the B27+ReA+ group than in the B27+ReA− or B27−ReA− group in response to PMA/A23187 (p values <0.001), and greater in the B27+ReA+ group than in the B27−ReA− group in response to LPS (p = 0.021). CD14 (−159)T was associated allele dose dependently with an increase in the LPS induced TNF secretion allele (p = 0.030). Conclusions: Subjects who have recovered from yersinia arthritis show enhanced TNF production, which may be regulated at the level of monocyte adhesion.